Atmospheric analogues for physically consistent scenarios of surface weather in Europe and Maghreb. (28th July 2016) - Raynaud, Damien; Hingray, Benoit; Zin, Isabella; Anquetin, Sandrine; Debionne, Samuel; Vautard, Robert
ABSTRACT: This study compares the multivariate predictions of daily temperature, temperature range, precipitation, surface wind and solar radiation of a single‐model analogue approach with an original multi‐model analogy over 12 regions in Europe and Maghreb. Both approaches are based on two‐level analogue models where atmospheric predictors are either dynamic or thermodynamic. In the multi‐model approach, independent analogue models with predictand‐specific predictors are used. In the single‐model one, a unique analogue model and its associated set of predictors is applied to all predictands. Testing numerous large‐scale predictors, we first identify the best predictor sets for each modelling strategy. Those obtained for the single‐model approach are significantly different from those of the predictand‐specific models. This is especially the case for local temperature and wind speed. Both methods perform similarly for precipitation, temperature range and radiation. We next assess the ability of both approaches to simulate physically coherent multivariate weather scenarios. With the single‐model method, weather scenarios are obtained for each prediction day from observations sampled simultaneously on one analogue day. The physical consistency between variables is thus automatically fulfilled each day. This allows the single‐model method to reproduce well the observed inter‐predictand correlations, especially the significant correlations between radiation and precipitation and between radiation and temperature range. These results suggest a hybrid analogue model using a single‐model for radiation, temperature range and precipitation, combined with a univariate approach for wind. Two options are proposed for temperature for which either the predictand‐specific method or a single‐model approach with an additional correction are conceivable. This hybrid approach leads to a possible compromise between reasonable univariate prediction skills and realistic inter‐predictands correlations, both classically required for many impact studies.